Lived Experience’s on Male Spouse of Patients with Lung Cancer in Indonesia - Dimas Ria Angga Pribadi; Hung Ru Lin (South East Asia Nursing Research, 2022)
Patients with advanced lung cancer might have a higher number of supportive care needs, when a married, middle-aged woman is diagnosed with this disease, her spouses most often become the primary caregiver. However few studies have explored the lived experiences of Male Spouses. This study aimed to explore the lived experience of male caregivers among lung cancer patients. The phenomenological method is adopted to obtain the male lived experiences of caregivers.” In-depth face-to-face interviews with the caregivers were the main source of data for this study. Five male caregivers completed the interview; all of the participant's spousal was diagnosed with lung cancer and are under a chemotherapy program. Content analysis of five participant interviews revealed four themes: (1) Facing difficulties, (2) Social activities interrupted, (3) a Sense of being responsible and needed and (4) Gaining support from family and God. This study explored the male caregiver lived experiences of five Indonesian patients with lung cancer. The findings pointed to the importance of considering multiple issues influencing male caregiver conditions while providing care.